2015
DOI: 10.12809/hkmj144292
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy and tolerance of short-duration open-ended ureteral catheter drainage and tamsulosin administration to indwelling double J stents following ureteroscopic removal of stones

Abstract: Objectives:To evaluate the efficacy of shortduration, open-ended ureteral catheter drainage as a replacement to indwelling stent, and to study the effect of tamsulosin on stent-induced pain and storage symptoms following uncomplicated ureteroscopic removal of stones.Design: Prospective randomised study.Setting: School of Medical Sciences and Research, Sharda University, Greater Noida, India. Patients:Patients who underwent ureteroscopic removal of stones for lower ureteral stones between November 2011 and Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…In other studies, it is defined that use of a stent is not beneficial with stones even larger than 1.0 cm. Moreover, our study confirmed these reports and concluded that stents do not interfere with stone-free rates after ESWL but enhance the stent-related complications such as steinstrasse and discomfort [18][19][20][21][22][23] . We recommend that routine usage of DJ stent after every ESWL should be minimized and only selected patients get DJ stenting after ESWL.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In other studies, it is defined that use of a stent is not beneficial with stones even larger than 1.0 cm. Moreover, our study confirmed these reports and concluded that stents do not interfere with stone-free rates after ESWL but enhance the stent-related complications such as steinstrasse and discomfort [18][19][20][21][22][23] . We recommend that routine usage of DJ stent after every ESWL should be minimized and only selected patients get DJ stenting after ESWL.…”
Section: Discussionsupporting
confidence: 89%
“…However, in the literature, there are no differences found in hospitalized and recovered patients after the stenting procedure 16,17 . Ureteral stents are associated with major symptoms including pain, LUTs, and reduced working capacity, which results in reduced quality of daily life, whereas ureteral stents, may cause pain and LUTs specifically dysuria, urgency and mild to moderate hematuria [18][19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Gonen et al showed that external ureteral catheters were more comfortable with the adult patients in a short time while being as reliable and safe as an indwelling stent (11). Vikram et al also reported that external open-ended ureteral catheter drainage was equally effective and better tolerated than routine stenting following the uncomplicated ureteroscopic removal of stones (12). In this study, we demonstrate that the placement of external ureteral catheters instead of double-J stents, is a viable option to relieve bilateral ureteral obstruction and provide short-term urine drainage.…”
Section: Discussionmentioning
confidence: 99%
“…In all, 14 studies did not meet the inclusion criteria or were not relevant to the question under question. 1,11,[16][17][18][19][20][21][22][23][24][25][26][27] We identified one ongoing trial. 28 In all, 23 studies with 24 relevant articles (abstracts or secondary publications: not listed in the references) ultimately met the inclusion criteria and were included in the qualitative synthesis of this review.…”
Section: Search Resultsmentioning
confidence: 99%